Infrared spectroscopy as an alternative methodology to evaluate the effect of structural features on the physical-chemical properties of inulins - Romano, Nelson Gastón (2018)
Two types of inulins of different composition were investigated in the glassy and in the crystalline states, at relative humidities within 11 and 97%. The melting and glass transition temperatures (Tm, Tg), and their crystallinity indexes (CI) were determined by modulated differential-scanning calorimetry (MDSC) and wide-angle X-ray scattering (WAXS), respectively. In parallel assays, Fourier transform-infrared spectroscopy (FTIR) coupled to principal component analysis (PCA) enabled a physical-chemical and structural characterization of samples, explaining 90% of the total variance. Finally, partial least square (PLS) models were defined to determine Tg, Tm, and CI directly from the FTIR spectra, using the MDSC and WAXS results as reference methods. In all cases, the mean of predicted values fitted very well those of the reference methods (R2 > 0.961), thus supporting the use of the PLS models to investigate unknown samples. The robustness of the models underlines the usefulness of FTIR to easily determine physical-chemical parameters, otherwise requiring complex preparation of samples and prolonged times of analysis.